2012
DOI: 10.1056/nejmoa1111097
|View full text |Cite
|
Sign up to set email alerts
|

Bevacizumab Added to Neoadjuvant Chemotherapy for Breast Cancer

Abstract: Background Bevacizumab and the antimetabolites capecitabine and gemcitabine have been shown to improve outcomes when added to taxanes in patients with metastatic breast cancer. The primary aims of this trial were to determine whether the addition of capecitabine or gemcitabine to neoadjuvant chemotherapy with docetaxel, followed by doxorubicin plus cyclophosphamide, would increase the rates of pathological complete response in the breast in women with operable, human epidermal growth factor receptor 2 (HER2)–n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
262
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(276 citation statements)
references
References 25 publications
9
262
2
3
Order By: Relevance
“…The pCR rate, defined as no invasive residuals in the breast, was 27.8%, which is comparable to 24.5% (21.9-27.4%) reached with bevacizumab in addition to EC followed by docetaxel in the GeparQuinto study, but slightly lower than 34.5% (30.7-38.3%) in the National Surgical Adjuvant Breast and Bowel Project (NSABP) B40 study [2,3]. The pCR rates, irrespective of the definitions, were slightly above those seen with bevacizumab [2,][3].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…The pCR rate, defined as no invasive residuals in the breast, was 27.8%, which is comparable to 24.5% (21.9-27.4%) reached with bevacizumab in addition to EC followed by docetaxel in the GeparQuinto study, but slightly lower than 34.5% (30.7-38.3%) in the National Surgical Adjuvant Breast and Bowel Project (NSABP) B40 study [2,3]. The pCR rates, irrespective of the definitions, were slightly above those seen with bevacizumab [2,][3].…”
Section: Discussionmentioning
confidence: 91%
“…The pCR rates, irrespective of the definitions, were slightly above those seen with bevacizumab [2,][3]. However, the sample size was smaller than initially planned in order to demonstrate an added effect.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[19][20][21] However, the mechanism for this improved response remains unclear and the literature surrounding vessel normalization in preclinical models is controversial. Multiple studies have demonstrated evidence of vessel normalization and increased therapeutic uptake.…”
Section: Discussionmentioning
confidence: 99%
“…The phase III GeparQuinto trial reported a significantly higher pCR rate for the combination of chemotherapy and bevacizumab in comparison to chemotherapy alone in this patient subgroup [30]. The NSABP B-40 trial, however, found this effect of bevacizumab predominantly in luminal HR-positive breast cancers [31]. Furthermore, the BEATRICE phase III trial investigated the antibody as an additional treatment to chemotherapy in unselected patients with TNBC, but did not show any benefit in this patient cohort [32].…”
Section: Future Perspectives Of Targeted Treatmentmentioning
confidence: 99%